2017
DOI: 10.1088/1361-6668/aa69ed
|View full text |Cite|
|
Sign up to set email alerts
|

3D magnetization currents, magnetization loop, and saturation field in superconducting rectangular prisms

Abstract: Bulk superconductors are used in both many applications and material characterization experiments, being the bulk shape of rectangular prism very frequent. However the magnetization currents are still mostly unknown for this kind of three dimensional (3D) shape, specially below the saturation magnetic field. Knowledge of the magnetization currents in this kind of samples is needed to interpret the measurements and the development of bulk materials for applications. This article presents a systematic analysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Appearance of a significant z component of j , necessary for shielding the zero-field core, is an unexpected feature of current density distribution discovered and explained in [16][17][18]. We found that smoothing, employed in the FFT-based method, smears the narrow peaks of z j and, therefore, had to use a weaker Gaussian filter with 0.5d   to arrive at the z j -distribution ( Figure 6) similar to that in [19].…”
Section: Bulk Magnetization: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appearance of a significant z component of j , necessary for shielding the zero-field core, is an unexpected feature of current density distribution discovered and explained in [16][17][18]. We found that smoothing, employed in the FFT-based method, smears the narrow peaks of z j and, therefore, had to use a weaker Gaussian filter with 0.5d   to arrive at the z j -distribution ( Figure 6) similar to that in [19].…”
Section: Bulk Magnetization: Simulation Resultsmentioning
confidence: 99%
“…To make the conducting and non-conducting domains simply connected, we introduced a cutting-hole layer . The iterations(18), intended to eliminate the stray outside current, were applied in out  but not in 0  . For e ( ) (0,0, ) tt  h the resistivity out 200   was sufficient to make the current in 0  negligibly small even without such iterations (see the hole || j levels inFigure 7, left).…”
mentioning
confidence: 99%
“…The trapped magnetic field B t during the whole process is calculated 1 mm above the top surface ( figure 11). After relaxation, we applied cross-fields with two different amplitudes, 40 and 240 mT, in order to see the behaviour in the fields below and above the penetration field B p of the stack. The parallel penetration field B p, of 1 tape is 17 mT according to the slab Critical-State model [50,51],…”
Section: Trapped Magnetic Field In the Stack Of Tapesmentioning
confidence: 99%
“…Here we solve such a 3D problem for a hollow superconducting cylinder sealed at one end (the configuration considered in [2]) using the Fast Fourier Transform (FFT) based method [6]. This method is an easily implemented alternative to the finite element methods for 3D magnetization problems (see, e.g., [7][8][9][10][11][12]) and we employ it to model also field concentration by a magnetic lens. The configuration of a bulk superconductor in the latter problem is that of the magnetic lenses in [13].…”
Section: Introductionmentioning
confidence: 99%